BY PRODUCT EXCHANGE OF SEAWEED SOLID WASTE FOR MUSHROOMS MEDIA - Titiresmi Adyananto (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2007)
A laboratory experiment on utilization of seaweed-containing solid wastes as media for growing mushrooms was conducted by researchers from the Institute for Environmental Technology. The solid wastes were obtained from PT. Agarindo Bogatama, a food industry which produces jelly powder processed from seaweed of Gracilaria. The company generates 60 tones of solid wastes of seaweed per-day that contained 70% of water content. The solid media was used to grow Auricularia polytricha, Pleurotus astreatus, and Ganoderma lucidum. Some mixed media were prepared with the percentage ratio of sawdust to solid waste as 0, 25, 50, 75, and 100. After sterilizationthe media were planted with mushrooms and then were kept in incubator. After 28-day the basidiomas of G. lucidum was developed while P. astreatus appeared after 36-day of incubation. Both were grown on 100% seaweed media (using 100% sawdust media as a control). This very early results indicated that solid waste of seaweeds have an additional value which can be used as media for mushrooms plantation. Implementation waste to product as a part of cleaner production approach should be disseminated to the industries, especially SMEs like PT. Agarindo Bogatama, who areconcern to the environment.